A mineral-filled PA6 composite material and its preparation method and use

By using modified mica powder and bisacetone acrylamide in PA6 composite materials, the problem of insufficient physical properties of PA6 composite materials in the prior art has been solved, and higher physical properties have been achieved, and it is suitable for high-performance automotive parts.

CN118421075BActive Publication Date: 2025-04-11HEFEI GENIUS NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310047618.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-31
Publication Date
2025-04-11
Estimated Expiration
2043-01-31

AI Technical Summary

Technical Problem

Existing mineral-filled PA6 composites lack physical performance in certain high-performance automotive parts, especially in applications such as automotive hub covers.

Method used

Modified mica powder is used as a mineral filler, and the surface of the mica powder is coated with titanium dioxide to form titanium dioxide-coated mica powder, and bisacetone acrylamide is added to PA6 to enhance physical binding force.

Benefits of technology

Through the use of modified mica powder, the problem of local stress concentration in PA6 composite materials is alleviated and the physical properties of the material are improved. It is suitable for high-performance automotive parts such as automotive hub covers.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a mineral-filled PA6 composite material, a preparation method and use thereof, wherein the mineral-filled PA6 composite material is prepared by weight from 80-100 parts of PA6, 1-3 parts of diacetone acrylamide, 10-20 parts of modified mica powder and 0.1-0.5 parts of an antioxidant; wherein the modified mica powder is titanium dioxide-coated mica powder. The mineral-filled PA6 composite material has excellent physical properties, can be applied to the preparation of automobile parts such as automobile hub covers, and has great development prospects and promotion value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer modified materials technology, specifically relating to a mineral-filled PA6 composite material, its preparation method, and its uses. Background Technology

[0002] Polyamide 6 (PA6), also known as Nylon 6, is a widely used high-molecular-weight polyester resin. Adding a certain amount of minerals to the PA6 system, through mineral filling, is an important method of PA6 modification. This results in PA6 composites with advantages such as good fatigue resistance, good heat resistance, easily controllable shrinkage, and good dimensional stability. However, it also generally suffers from relatively low physical properties. In certain specific fields, such as automotive wheel covers, higher physical properties of PA6 are often required. Summary of the Invention

[0003] In view of this, the present invention needs to provide a mineral-filled PA6 composite material, which has excellent physical properties and can be applied to automotive parts such as wheel covers.

[0004] To achieve the above objectives, the present invention adopts the following technical solution:

[0005] The present invention first provides a mineral-filled PA6 composite material, which is prepared by weight of 80-100 parts of PA6, 1-3 parts of diacetone acrylamide, 10-20 parts of modified mica powder and 0.1-0.5 parts of antioxidant; wherein the modified mica powder is titanium dioxide coated mica powder.

[0006] In a further embodiment, the preparation of the modified mica powder includes the following steps:

[0007] Mica powder, acetone solvent, deionized water, sodium titanate and polyethylene glycol are mixed and reacted to obtain a mixed solution;

[0008] Saturated ammonium chloride solution was slowly added to the mixed solution to adjust its pH to neutral. The solution was then washed, filtered, and dried to obtain modified mica powder.

[0009] The specific reaction process is as follows:

[0010] Na4TiO4+4H2O→H4TiO4+4NaOH;

[0011] H4TiO4→TiO2+2H2O.

[0012] Through the above reaction process, the generated TiO2 coats the surface of the mica powder, forming titanium dioxide coated mica powder.

[0013] In a further embodiment, the mixing reaction specifically involves mixing and stirring at 40-60°C for 6-8 hours.

[0014] In a further embodiment, the mass ratio of mica powder, acetone, deionized water, sodium titanate and polyethylene glycol is (30-40):(80-100):(120-160):(40-50):(6-8).

[0015] In a further embodiment, the antioxidant is selected from one or a mixture of two or more of antioxidants 168, antioxidant 1010, and antioxidant 1330.

[0016] This invention further provides a method for preparing the mineral-filled PA6 composite material as described above, comprising the following steps:

[0017] Weigh PA6, diacetone acrylamide, modified mica powder and antioxidant according to the weight ratio, mix thoroughly to obtain a uniform mixture;

[0018] The mixture was added to a twin-screw extruder for extrusion granulation to obtain a mineral-filled PA6 composite material.

[0019] In a further embodiment, the twin-screw extruder includes six temperature zones arranged sequentially: zone 1 temperature 200–220℃, zone 2 temperature 260–280℃, zone 3 temperature 260–280℃, zone 4 temperature 260–280℃, zone 5 temperature 260–280℃, zone 6 temperature 260–280℃, and die head temperature 260–280℃; and / or, the screw speed is 200–280 r / min.

[0020] The present invention further provides the application of the mineral-filled PA6 composite material as described above or the mineral-filled PA6 composite material prepared by the aforementioned preparation method in the preparation of automotive parts.

[0021] The present invention also provides an automotive component, which is made of the mineral-filled PA6 composite material as described above or the mineral-filled PA6 composite material prepared by the aforementioned preparation method.

[0022] In a further embodiment, the automotive component is a wheel hub cover.

[0023] The present invention has the following beneficial effects:

[0024] In this invention, modified mica powder is used as a mineral filler in the PA6 system, that is, titanium dioxide is used to coat the mica powder. After the mica powder is coated with titanium dioxide, its sharp edges become blunt and its smooth cleavage surface becomes rough, which alleviates the problem of local stress concentration in the PA6 composite material. At the same time, the titanium dioxide coated on the surface of the mica powder also enhances the interfacial force between the mica powder and the PA6 matrix, thereby improving the physical properties of the PA6 composite material.

[0025] In this invention, diacetone acrylamide is also added to the PA6 system. The C=O and NH groups of diacetone acrylamide can form hydrogen bonds with the -OH groups on the surface of mica powder. The formation of hydrogen bonds can improve the physical bonding force between the PA6 matrix and the mica powder, thereby improving the physical properties of PA6.

[0026] The mineral-filled PA6 composite material in this invention has excellent physical properties and can be used as a material for automobile wheel covers, showing great development prospects and promotional value. Detailed Implementation

[0027] The present invention will be described below through specific embodiments. It should be noted that the specific embodiments below are for illustrative purposes only and do not limit the scope of the present invention in any way. In addition, unless otherwise specified, methods that do not specifically describe conditions or steps are conventional methods, and the reagents and materials used can be obtained commercially.

[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.

[0029] The raw material information used in the following embodiments and comparative examples is as follows. It should be understood that the following raw materials are only examples to make the technical solutions in the embodiments clearer, and do not mean that the present invention can only use the following raw materials. The specific scope of protection of the claims shall prevail.

[0030] PA6 (grade PO247), Shenma; Acetone, Tianjin Fuyu Fine Chemical Co., Ltd.; Deionized water, Shanghai Jingchun Water Treatment Technology Co., Ltd.; Sodium titanate, Shanghai Aladdin Biochemical Technology Co., Ltd.; Mica powder (800 mesh), Chuzhou Gree Mining Co., Ltd.; Polyethylene glycol, Nanjing Xingsha Chemical Co., Ltd.; Saturated ammonium chloride solution, prepared by the laboratory; Diacetone acrylamide, Weifang Sesame Open Chemical Co., Ltd.; Antioxidants (models Irganox 168, Irganox 1010, Irganox 1330), BASF AG, Germany.

[0031] Example 1

[0032] Preparation of modified mica powder

[0033] (1) Weigh 300g mica powder, 800g acetone, 1.2kg deionized water, 400g sodium titanate and 60g polyethylene glycol, put them into a reactor dish, mix and stir evenly at 40℃ for 6h to obtain solution A;

[0034] (2) Weigh a certain amount of solution A, slowly add saturated ammonium chloride solution to the reactor vessel, adjust its pH value to neutral, wash, filter and dry to obtain modified mica powder, which is recorded as M1.

[0035] Preparation of PA6 composite materials

[0036] (1) Weigh 80 parts of PA6, 1 part of diacetone acrylamide, 10 parts of modified mica powder M1 and 0.1 parts of antioxidant Irganox1010 according to the weight, mix and stir evenly to obtain a mixture;

[0037] (2) The mixture obtained in step (1) is added to a twin-screw extruder for extrusion granulation to obtain PA6 composite material, denoted as P1;

[0038] The temperatures and screw speeds of the twin-screw extruder in each zone are as follows: Zone 1 temperature 200℃, Zone 2 temperature 260℃, Zone 3 temperature 260℃, Zone 4 temperature 260℃, Zone 5 temperature 260℃, Zone 6 temperature 260℃, and Die head temperature 260℃; screw speed 200r / min.

[0039] Example 2

[0040] Preparation of modified mica powder

[0041] (1) Weigh 400g mica powder, 1.0kg acetone, 1.6kg deionized water, 500g sodium titanate and 80g polyethylene glycol, put them into a reactor dish, mix and stir evenly at 60℃ for 8h to obtain solution A;

[0042] (2) Weigh a certain amount of solution A, slowly add saturated ammonium chloride solution to the reactor vessel, adjust its pH value to neutral, wash, filter and dry to obtain modified mica powder, which is denoted as M2.

[0043] Preparation of PA6 composite materials

[0044] (1) Weigh 90 parts of PA6, 1.5 parts of diacetone acrylamide, 15 parts of modified mica powder M2, 0.1 parts of antioxidant Irganox1010, and 0.2 parts of antioxidant Irganox168 according to the weight ratio, mix and stir evenly to obtain a mixture;

[0045] (2) The mixture obtained in step (1) is added to a twin-screw extruder for extrusion granulation to obtain PA6 composite material, denoted as P2;

[0046] The temperatures and screw speeds of the twin-screw extruder in each zone are as follows: Zone 1 temperature 220℃, Zone 2 temperature 280℃, Zone 3 temperature 280℃, Zone 4 temperature 280℃, Zone 5 temperature 280℃, Zone 6 temperature 280℃, and die head temperature 280℃; screw speed 280r / min.

[0047] Example 3

[0048] Preparation of modified mica powder

[0049] (1) Weigh 350g mica powder, 900g acetone, 1.4kg deionized water, 450g sodium titanate and 70g polyethylene glycol, put them into a reactor dish, mix and stir evenly at 50℃ for 7h to obtain solution A;

[0050] (2) Weigh a certain amount of solution A, slowly add saturated ammonium chloride solution to the reactor vessel, adjust its pH value to neutral, wash, filter and dry to obtain modified mica powder, which is denoted as M3.

[0051] Preparation of PA6 composite materials

[0052] (1) Weigh 100 parts PA6, 3 parts diacetone acrylamide, 20 parts modified mica powder M3 and 0.2 parts antioxidant Irganox1330, 0.1 parts antioxidant Irganox168 and 0.2 parts antioxidant Irganox1010 according to the weight, mix and stir evenly to obtain a mixture;

[0053] (2) The mixture obtained in step (1) is added to a twin-screw extruder for extrusion granulation to obtain PA6 composite material, denoted as P3;

[0054] The temperatures and screw speeds of the twin-screw extruder in each zone are as follows: Zone 1 temperature 210℃, Zone 2 temperature 270℃, Zone 3 temperature 270℃, Zone 4 temperature 270℃, Zone 5 temperature 270℃, Zone 6 temperature 270℃, and die head temperature 270℃; screw speed 240r / min.

[0055] Example 4

[0056] Preparation of modified mica powder

[0057] (1) Weigh 380g mica powder, 890g acetone, 1.3kg deionized water, 420g sodium titanate and 65g polyethylene glycol, put them into a reactor dish, mix and stir evenly at 45℃ for 8h to obtain solution A;

[0058] (2) Weigh a certain amount of solution A, slowly add saturated ammonium chloride solution to the reactor vessel, adjust its pH value to neutral, wash, filter and dry to obtain modified mica powder, which is denoted as M4.

[0059] Preparation of PA6 composite materials

[0060] (1) Weigh 95 parts of PA6, 2 parts of diacetone acrylamide, 18 parts of modified mica powder M4, 0.2 parts of antioxidant Irganox1330, and 0.1 parts of antioxidant Irganox168 according to the weight, mix and stir evenly to obtain a mixture;

[0061] (2) The mixture obtained in step (1) is added to a twin-screw extruder for extrusion granulation to obtain PA6 composite material, denoted as P4;

[0062] The temperatures and screw speeds of the twin-screw extruder in each zone are as follows: Zone 1 temperature 215℃, Zone 2 temperature 270℃, Zone 3 temperature 270℃, Zone 4 temperature 270℃, Zone 5 temperature 270℃, Zone 6 temperature 270℃, and die head temperature 270℃; screw speed 250r / min.

[0063] Example 5

[0064] Preparation of modified mica powder

[0065] (1) Weigh 390g mica powder, 920g acetone, 1.5kg deionized water, 490g sodium titanate and 75g polyethylene glycol, put them into a reactor dish, mix and stir evenly at 55℃ for 6h to obtain solution A;

[0066] (2) Weigh a certain amount of solution A, slowly add saturated ammonium chloride solution to the reactor vessel, adjust its pH value to neutral, wash, filter and dry to obtain modified mica powder, which is denoted as M5.

[0067] Preparation of PA6 composite materials

[0068] (1) Weigh 85 parts of PA6, 1 part of diacetone acrylamide, 13 parts of modified mica powder M5 and 0.1 parts of antioxidant Irganox1010 and 0.1 parts of antioxidant Irganox168 according to the weight, mix and stir evenly to obtain a mixture;

[0069] (2) The mixture obtained in step (1) is added to a twin-screw extruder for extrusion granulation to obtain PA6 composite material, denoted as P5;

[0070] The temperatures and screw speeds of the twin-screw extruder in each zone are as follows: Zone 1 temperature 205℃, Zone 2 temperature 275℃, Zone 3 temperature 275℃, Zone 4 temperature 275℃, Zone 5 temperature 275℃, Zone 6 temperature 275℃, and die head temperature 275℃; screw speed 245r / min.

[0071] Comparative Example 1

[0072] In this comparative example, the PA6 composite material was prepared using the same method as in Example 5, except that the mica powder used was not modified. The specific steps are as follows:

[0073] (1) Weigh 85 parts of PA6, 1 part of diacetone acrylamide, 13 parts of unmodified mica powder, 0.1 parts of antioxidant Irganox1010, and 0.1 parts of antioxidant Irganox168 according to the weight ratio, mix and stir evenly to obtain a mixture;

[0074] (2) The mixture obtained in step (1) is added to a twin-screw extruder for extrusion granulation to obtain PA6 composite material, denoted as D1;

[0075] The temperatures and screw speeds of the twin-screw extruder in each zone are as follows: Zone 1 temperature 205℃, Zone 2 temperature 275℃, Zone 3 temperature 275℃, Zone 4 temperature 275℃, Zone 5 temperature 275℃, Zone 6 temperature 275℃, and die head temperature 275℃; screw speed 245r / min.

[0076] Comparative Example 2

[0077] In this comparative example, the PA6 composite material was prepared using the same method as in Example 5, except that diacetone acrylamide was not added. The specific steps are as follows:

[0078] (1) Weigh 85 parts of PA6, 13 parts of modified mica powder M5 and 0.1 parts of antioxidant Irganox1010 and 0.1 parts of antioxidant Irganox168 according to the weight parts, mix and stir evenly to obtain a mixture;

[0079] (2) The mixture obtained in step (1) is added to a twin-screw extruder for extrusion granulation to obtain PA6 composite material, denoted as D2;

[0080] The temperatures and screw speeds of the twin-screw extruder in each zone are as follows: Zone 1 temperature 205℃, Zone 2 temperature 275℃, Zone 3 temperature 275℃, Zone 4 temperature 275℃, Zone 5 temperature 275℃, Zone 6 temperature 275℃, and die head temperature 275℃; screw speed 245r / min.

[0081] Comparative Example 3

[0082] The PA6 composite material in this comparative example was prepared using the same method as in Example 5, except that diacetone acrylamide was not added, and the mica powder was not modified. The specific steps are as follows:

[0083] (1) Weigh 85 parts of PA6, 13 parts of unmodified mica powder, 0.1 parts of antioxidant Irganox1010, and 0.1 parts of antioxidant Irganox168 according to the weight ratio, mix and stir evenly to obtain a mixture;

[0084] (2) The mixture obtained in step (1) is added to a twin-screw extruder for extrusion granulation to obtain PA6 composite material, denoted as D3;

[0085] The temperatures and screw speeds of the twin-screw extruder in each zone are as follows: Zone 1 temperature 205℃, Zone 2 temperature 275℃, Zone 3 temperature 275℃, Zone 4 temperature 275℃, Zone 5 temperature 275℃, Zone 6 temperature 275℃, and die head temperature 275℃; screw speed 245r / min.

[0086] Performance testing

[0087] The PA6 composite materials obtained in Examples 1-5 and Comparative Examples 1-3 were injection molded into specimens for relevant performance tests. The test results are shown in Table 1.

[0088] Table 1. Performance test results of PA6 composite material

[0089] Test Project Tensile strength Flexural modulus Cantilever beam impact strength Test Standards GB / T 1040.1 / 2 GB / T 9341 GB / T 1843 unit MPa MPa <![CDATA[kJ / m 2 ]]> P1 89.3 4033 4.1 P2 87.7 4021 4.2 P3 88.8 4110 3.7 P4 88.2 4165 3.8 P5 87.5 4091 3.9 D1 77.1 3680 2.5 D2 75.3 3572 2.3 D3 76.4 3664 2.4

[0090] As can be seen from the test results in Table 1, the physical properties of the PA6 composite materials in Examples 1-5 are all better than those in Comparative Examples 1-3, indicating that the PA6 composite material in this invention has excellent physical properties and is very suitable for manufacturing automotive parts such as wheel covers, thereby expanding the application field of PA6 composite materials.

[0091] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0092] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A mineral-filled PA6 composite material, characterized in that: It is prepared from 80-100 parts of PA6, 1-3 parts of diacetone acrylamide, 10-20 parts of modified mica powder and 0.1-0.5 parts of antioxidant in parts by weight; wherein the modified mica powder is titanium dioxide coated mica powder; The preparation of the modified mica powder comprises the following steps: Mixing mica powder, acetone, deionized water, sodium titanate and polyethylene glycol to obtain a mixed solution; Saturated ammonium chloride solution is slowly added to the mixed solution to adjust the pH value to neutral, and the mixed solution is washed, filtered and dried to obtain modified mica powder.

2. The mineral-filled PA6 composite material according to claim 1, characterized in that: The mixing reaction is specifically: mixing and stirring at 40-60° C. for 6-8 hours.

3. The mineral-filled PA6 composite material according to claim 1, characterized in that: The mass ratio of the mica powder, acetone, deionized water, sodium titanate and polyethylene glycol is (30-40): (80-100): (120-160): (40-50): (6-8).

4. The mineral-filled PA6 composite material according to claim 1, characterized in that: The antioxidant is selected from one of antioxidant 168, antioxidant 1010, and antioxidant 1330, or a mixture of two or more thereof.

5. A method for preparing a mineral-filled PA6 composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: PA6, diacetone acrylamide, modified mica powder and antioxidant were weighed and mixed in proportion by weight to obtain a uniform mixture; The mixed material is added into a twin-screw extruder for extrusion and granulation to obtain a mineral-filled PA6 composite material.

6. The preparation method according to claim 5, characterized in that: The twin-screw extruder includes six temperature zones arranged in sequence: zone one temperature 200-220°C, zone two temperature 260-280°C, zone three temperature 260-280°C, zone four temperature 260-280°C, zone five temperature 260-280°C, zone six temperature 260-280°C, and a die head temperature of 260-280°C; and / or a screw speed of 200-280r / min.

7. Use of the mineral-filled PA6 composite material according to any one of claims 1 to 4 or the mineral-filled PA6 composite material prepared by the preparation method according to claim 5 or 6 in the preparation of automobile parts.

8. An automobile component, characterized in that: The invention is prepared by using the mineral-filled PA6 composite material as described in any one of claims 1 to 4 or the mineral-filled PA6 composite material prepared by the preparation method described in claim 5 or 6.

9. The automotive component according to claim 8, characterized in that: The automobile component is an automobile hub cover.

Citation Information

Patent Citations

  • Antibacterial and high-performance PS composite material and preparation method thereof

    CN106479074A

  • High-performance antibacterial polystyrene (PS) composite and preparation method thereof

    CN107189249A